2006
DOI: 10.1509/jmkg.70.1.119.qxd
|View full text |Cite
|
Sign up to set email alerts
|

Value-Based Differentiation in Business Relationships: Gaining and Sustaining Key Supplier Status

Abstract: Many business customers today consolidate their supply bases and implement preferred supplier programs. Consequently, vendors increasingly face the alternative of either gaining a key supplier status with their customers or being pushed into the role of a backup supplier. As product and price become less important differentiators, suppliers of routinely purchased products search for new ways to differentiate themselves in a buyer-seller relationship. This research investigates avenues for differentiation throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
773
4
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 419 publications
(816 citation statements)
references
References 49 publications
32
773
4
7
Order By: Relevance
“…Depth interviews have been used effectively in the marketing literature, especially in the business-to-business context when limited research is available (Flint et al 2002;Madhavan and Grover 1998;Tuli et al 2007;Ulaga and Eggert 2006). The use of a single firm for data collection is consistent with an empirical research tradition examining intricate process phenomena (DeCarlo et al 1997;Dixon et al 2005;Dixon et al 2003;Houston et al 2001).…”
Section: Data Collection and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Depth interviews have been used effectively in the marketing literature, especially in the business-to-business context when limited research is available (Flint et al 2002;Madhavan and Grover 1998;Tuli et al 2007;Ulaga and Eggert 2006). The use of a single firm for data collection is consistent with an empirical research tradition examining intricate process phenomena (DeCarlo et al 1997;Dixon et al 2005;Dixon et al 2003;Houston et al 2001).…”
Section: Data Collection and Samplementioning
confidence: 99%
“…Given the limited literature on coordination of expertise, following Ulaga and Eggert (2006) in a two-phase study, we first conducted depth interviews with 60 salespeople at a Fortune-100 high-technology firm, using a grounded theory approach (Glaser and Strauss 1967), to gain managerial insights into the processes and strategies that salespeople use to coordinate expertise for both successful and unsuccessful customer engagements. Using this data, in Phase I we identify the processes involved in the coordination of expertise in the selling context and create a measure of the coordination of expertise.…”
mentioning
confidence: 99%
“…For example, Cannon and Homburg (2001) identified three sources of value creation through cost reductions in business relationships: the core product, the sourcing process, and the customer firm's internal operations. Based on empirical results, Ulaga and Eggert (2006) demonstrated that this categorization of value sources is not limited to cost reductions but also applies to generic benefit dimensions.…”
Section: Relationship-oriented Pcvmentioning
confidence: 99%
“…The benefit dimension is often expanded to include process utility components, particularly aspects of the post-purchase phase (e. g., supply, maintenance, warranty) in order to take into account temporal components (see Lai 1995;Ravald and Grönroos 1996;Huber et al 2001;Chen and Dubinsky 2003;Eggert et al 2006). However, the pre-purchase phase can likewise significantly influence PCV, as, for example the empirical study of Chen and Dubinsky (2003) in the area of eBusiness shows.…”
Section: Relationship-oriented Pcvmentioning
confidence: 99%
See 1 more Smart Citation